Réponses

2013-11-12T18:49:43+01:00
A= -2(x-5)+3(-7-x)
=-2x+10-21-3x
=-5x-11

B= x(2x-6)-(2-x²)
=2x²-6x-2+x²
=3x²-6x-2

C= -x(4+3x)-(x²-2+5x)
=-4x-3x²-x²+2-5x
=-8x²-5x+2
2013-11-12T19:00:43+01:00
a= -2(x-5)+3(-7-x)
a=-2x+10-21-3x
a=-5x-11              
                               b= x(2x-6)-(2-x²)
                               b=2x²-6x-2+x²
                                b=3x²-6x-2
 
                                                           c= -x(4+3x)-(x²-2+5x)
                                                           c=-4x-3x²-x²+2-5x
                                                           c=-8x²-5x+2